2013
DOI: 10.1155/2013/685174
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hemocoagulation Disorders on the Development of Posttraumatic Cerebral Infarction and Outcome in Patients with Moderate or Severe Head Trauma

Abstract: Posttraumatic cerebral infarction (PTCI) is a severe secondary insult of head injury and often leads to a poor prognosis. Hemocoagulation disorder is recognized to have important effects on hemorrhagic or ischemic damages. We sought to assess if posttraumatic hemocoagulation disorders were associated with cerebral infarction, and evaluate their influence on outcome among patients with moderate or severe head trauma. In this study, PTCI was observed in 28 (10.57%) of the 265 patients within the first week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Previous studies were either post-mortem neuropathological investigations or ante-mortem retrospective clinical investigations. Among the latter, the GOS was assessed in four single-center studies at 3 months [5] or 6 months [4,9]; while in one study, the timing of the GOS was not reported [8]. These studies showed increased morbidity [4], increased mortality [9], increased morbidity and mortality [8], or no difference [5] in patients with a PTCI compared with patients without.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies were either post-mortem neuropathological investigations or ante-mortem retrospective clinical investigations. Among the latter, the GOS was assessed in four single-center studies at 3 months [5] or 6 months [4,9]; while in one study, the timing of the GOS was not reported [8]. These studies showed increased morbidity [4], increased mortality [9], increased morbidity and mortality [8], or no difference [5] in patients with a PTCI compared with patients without.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, the GOS was assessed in four single-center studies at 3 months [5] or 6 months [4,9]; while in one study, the timing of the GOS was not reported [8]. These studies showed increased morbidity [4], increased mortality [9], increased morbidity and mortality [8], or no difference [5] in patients with a PTCI compared with patients without. In three of these studies [4,5,9], the impact of a PTCI was assessed while considering the role of other predicting variables, such as age and GCS, using multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we weren't able to identify the individualized risk factors for each factor due to the small number size. Several studies have demonstrated that FVIIa might represent a risk factor in certain patients groups [24], while others weren't able to find evidence in applying fibrinogen concentrate or rFVIIa [25] associated with a higher risk for thrombotic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, DIC is not an independent disease, but a pathologic process induced by certain factors on the basis of certain diseases. [44][45][46] Patients suffering from CHD prompted the existent of atherosclerosis, and when they have elevated D-dimer levels, they more likely to have high blood coagulation state. And the happening of AICVD usually associated with plaque rupture and/ or hemodynamic changes.…”
Section: Non-chd Groupmentioning
confidence: 99%